Bands of brothers: a re‐appraisal of the Viking Great Army and its implications for the Scandinavian colonization of England. Issue 3 (August 2016) - Raffield, Ben
Abstract : Although the ninth‐century Viking Great Army has been subject to intensive historical and archaeological study, it remains an enigmatic entity. This article explores the evidence for the Great Army in England through the consideration of archaeological materials in addition to the organizational structures underpinning the formation of Viking 'armies'. In light of this, I argue that the Great Army is better considered as a mobile society or polity rather than an armed force. Viewing the Great Army in this way influences not only the interpretation of evidence recovered in the field, but also our understanding of the Scandinavian settlement of northern and eastern England during the late ninth century.